Conselhos gestores e gestão pública - Maria da Glória Gohn (Ciências Sociais Unisinos, 2006)
The article analise the councils in the context of construction of democracy and popular participation. From a historical backtracking of the its presence in public administration in Brazil, the text discusses the changing occurred in such organisms and the current debate about its role. The article signs as well the existing gaps in the process of participation in these councils. Furthermore it indicates the need of research and evaluations of its performance and the impact of its actions on the society and the State.